THE IMPORTANCE OF LEARNING FOREIGN LANGUAGES IN THE ERA OF GLOBALIZATION. (Ta'limning zamonaviy transformatsiyasi, 2024)
Annotation: This article delves into the significance of learning foreign languages in the context of globalization. It examines the cognitive, economic, and cultural benefits of language acquisition while addressing the challenges learners face. Practical strategies such as technology integration, immersive learning, and enhanced educational policies are also discussed to provide a roadmap for effective language learning in the modern era.